Studi tentang Pelaku Homoseksual di Kota Serang: Studi Kasus pada Tiga Orang Pria Teridentifikasi Homoseksual di Kota Serang - Meilla Dwi Nurmala; Penta Aruna Rosadi; Deasy Yunika Khairun (Ma'soem University, 2022)
This research is motivated by the problem of homosexual deviation in Serang City. The aims of the study were to determine the description of homosexuality in Serang City, to determine the dominant factors behind individuals becoming homosexual offenders, and to determine alternative guidance and counseling services that could be provided by counselors to individual homosexual offenders in Serang City. This research uses a qualitative approach with case study research methods. Determination of informants in this study using the purposive method. The setting of this research was conducted in Serang City. The method in this study uses a qualitative approach. This means that the data collected is not calculated data using statistical procedures but in the form of narratives obtained from the results of interviews, observations, personal documents or other information that can complement the data being studied or in other words, the data and analysis are more qualitative in nature. The number of subjects three men who live in the city of Serang. The data collection technique was done by using source triangulation and member check methods. The data analysis technique used is an interactive model consisting of data reduction, data display (data display), and drawing conclusions, data analysis is carried out using research coding. The results show that homosexuals in Serang City tend to be secretive in their activities and have not come out yet. The dominant factor behind the informant being homosexual is a traumatic experience, especially with the father. Besides that, there are other factors, namely the influence of hormones, an unfavorable social environment, and the experience of sexual relations with individuals of the same sex. Alternative guidance and counseling that can be given by counselors to homosexual perpetrators in Serang City is counseling services with a psychoanalytic approach or with a rational emotive therapy (RET) approach.